1976
DOI: 10.1079/bjn19760005
|View full text |Cite
|
Sign up to set email alerts
|

The induction of obesity in rodents by means of monosodium glutamate

Abstract: I. Monosodium glutamate (MSG) was administered by various methods to mice and rats of various ages and the incidence of obesity was later measured.2. Newborn mice were injected subcutaneously with 3 mg MSG/g body-weight at I, 2 , 3, 6, 7 and 8 d of age: 16% died before weaning. Of the survivors, 90% or more became markedly obese. Mean carcass lipid content was increased by about I Z O~~ in both sexes at 2-30 weeks of age. In male mice, MSG treatment increased body-weight and epididymal fat pad weight, and grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
2
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 15 publications
6
70
2
2
Order By: Relevance
“…In connection with the development of obesity, the balance between energy supply and expenditure should be taken into consideration. In regard to the energy supply, no hyperphagia was demonstrated in the MSG-treated mice (2,3,20). Hyperplasia of the intestine, noted after 8 weeks of age, suggests a possible acceleration of the absorptive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with the development of obesity, the balance between energy supply and expenditure should be taken into consideration. In regard to the energy supply, no hyperphagia was demonstrated in the MSG-treated mice (2,3,20). Hyperplasia of the intestine, noted after 8 weeks of age, suggests a possible acceleration of the absorptive function.…”
Section: Discussionmentioning
confidence: 99%
“…In the same report, he mentioned that the animals with MSG-induced hypothalamic lesions became apparently obese in and after adolescence even without hyperphagia and that these MSG-induced obese animals remained short throughout their lives (1)(2)(3)(4). MSG-induced obese animals have been mainly investigated biochemically in order to clarify the mechanism of obesity (5)(6)(7)(8)(9) In the present study, the growth pattern of the visceral organs together with the changes in body weight gain, morphological findings and cell proliferative kinetics was investigated in MSG-induced obese mice.…”
mentioning
confidence: 99%
“…Therefore, it is responsible, at least in part, for the increase of glucocorticoids found in these adult rats 16,17 . MSG can be administered subcutaneously or intraperitoneally 18,19 at doses that vary by 2-4 mg/g of body weight of the rat during the neonatal period and for periods ranging by 4-10 doses causing obesity [20][21][22][23][24] . Since MSG is a substance found in several foods consumed daily, it has been targeted by studies on its effects when taken orally.…”
Section: Monosodium Glutamate (Msg)mentioning
confidence: 99%
“…Saline injection did not result in death of any of the group C animals. The early death of the MSG-injected animals was also reported in another investigation (Bunyan et al, 1976) and is routinely observed in other MSG-treated rats of our laboratory. This is probably due to the injection being made at the cervical region, very close to the developing Central Nervous System, and to the natural fragility of the newborn rats.…”
Section: Discussion Discussion Discussionmentioning
confidence: 74%